From Jesusita to Jane: Personal names, self-presentation and digital preservation of Mexican American experience in the US Midwest - Isasi Velasco, Jennifer; Velázquez, Isabel; Avelar, Janette (Revista de Humanidades Digitales, 2018)
Pairing preservation with analytical endeavors, the corpus for the present analysis consists of 345 digital objects that include one or more iterations of the personal name of the mother and daughter of a Mexican American family that migrated from Zacatecas, Mexico, to the American Midwest, during the first half of the 20th Century. Data were analyzed along the following dimensions: self-presentation, language(s), geographical location, temporality, public/private space, and type of text. At the same time, we describe the challenges involved in encoding names that follow different naming conventions, that were produced by speakers of two different languages, and that changed over time. We seek to contribute these voices to the scarcely studied social history of Mexican Americans in the Midwest. Aunando conservación con esfuerzos analíticos, el corpus del presente análisis consiste en 345 objetos digitales que incluye una o más iteraciones del nombre de la madre y la hija de una familia mexicano estadounidenses que migró de Zacatecas, México al Medio Oeste estadounidense, durante la primera mitad del siglo XX. Los datos han sido analizados en las siguientes dimensiones: autopresentación, lenguaje(s), localización geográfica, temporalidad, espacio público/privado y tipo de texto. Al mismo tiempo, describimos los retos del marcado de nombres que siguen diferentes convenciones, que fueron producidos por hablantes de diferentes idiomas y que cambiaron con el tiempo. Buscamos añadir estas voces a la poco estudiada historia social de los mexicano-americanos en el Medio Oeste.